(untitled) (Fiep Bulletin - online, 2012)
This paper describes the creation and action of CONFEF – Conselho Nacional de Educação Física e dos Conselhos Regionais de Educação Física – CREFs (Physical Education Brazilian Council and Physical Education Regional Councils). This institution has always worked for the credibility of the physical education professionals and for the establishment of legal regulations for the profession. In order to reach its objective, the institution has made social and educational agreements with several segments in society, has made alliances with the federal government, more specifically with the CNE (Conselho Nacional de Educação - Brazilian Council of Education) and has made arrangements with other professional councils. It now integrates the Permanent Forum of the Brazilian Council in the Health Area (Fórum Permanente do Conselho Federal na Área da Saúde). CONFEF also has agreements with agencies, sports entities and college education public institutions to evaluate physical education professionals and to inspect the their legal practice. It also promotes public anti doping campaigns. The results of CONFEF actions can be measured through several conquests such as the promulgation of legal regulations for the professional practice and for the routine activities in sports clubs and gymnasiums; the law that makes school physical education mandatory; the legal demand of physical education degree for coaches; the visibility of physical education professionals in society, where their importance, value and responsibility are now fully acknowledged.